1988
DOI: 10.1111/j.1600-0676.1988.tb00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transfusional vs. sporadic non‐A, non‐B chronic hepatitis. A clinico‐pathological and evolutive study

Abstract: ABSTRACT— The clinical, morphological and evolutive features of 60 patients with chronic hepatitis, presumably caused by non‐A, non‐B virus infection, have been retrospectively analyzed. In all the cases the disease began as an acute episode of viral hepatitis that was followed by persistently abnormal liver function tests. No patient had evidence of current or past hepatitis B virus infection and other known causes of chronic liver disease were excluded. Thirty patients had received blood transfusions in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The sporadic HNANB group (defined as not associated with transfusions or illicit self-injections) in this study were histologically followed for a mean of 44 months, when 41% had CAH and 23% signs of cirrhosis. In agreement with this, JovC et al found that 28% of patients with sporadic chronic NANB hepatitis exhibited a biopsy consistent with CAH after a mean follow-up of 15 months (15). None of the patients of Jove et al, however, developed cirrhosis, whereas 23% (51 22) of our patients developed fibrosis.…”
Section: Discussionsupporting
confidence: 88%
“…The sporadic HNANB group (defined as not associated with transfusions or illicit self-injections) in this study were histologically followed for a mean of 44 months, when 41% had CAH and 23% signs of cirrhosis. In agreement with this, JovC et al found that 28% of patients with sporadic chronic NANB hepatitis exhibited a biopsy consistent with CAH after a mean follow-up of 15 months (15). None of the patients of Jove et al, however, developed cirrhosis, whereas 23% (51 22) of our patients developed fibrosis.…”
Section: Discussionsupporting
confidence: 88%
“…Whether the route of transmission is an informative prognostic factor for HCV disease remains controversial. Several adult studies have indicated that transfusion‐associated hepatitis C (TAC) is histologically more severe than hepatitis C from intravenous drug use [15–18]. Furthermore, TAC was more likely than nontransfusion‐associated hepatitis C (non‐TAC) to result in liver failure [19].…”
Section: Introductionmentioning
confidence: 99%